IMPLICATIONS OF TURNOVER ON THE PROFITABILITY OF MEDIUM-SIZED FARMS IN ROMANIA - Paula STOICEA; Elena TOMA; Adina Magdalena IORGA; Carina DOBRE; Ramona Iuliana IGNAT (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The main economic objective of farms in Romania is to maximize turnover, this indicator being identified as the main source of profit growth. This paper analyses the turnover of a medium-sized vegetal farm, which is classified as a micro-enterprise for tax purposes. The data were collected from the enterprise accounting regarding the balance sheet and profit and loss account and rate method was used to assess the impact of turnover on various financial indicators. To increase turnover, the medium-sized vegetal farm acts in accordance with its own needs for development and expansion on the market, the conclusion being that an advantageous position on the market is interdependent with an increased turnover and therefore with greater profitability.